1995
DOI: 10.1002/esp.3290200403
|View full text |Cite
|
Sign up to set email alerts
|

Air flow over foredunes and implications for sand transport

Abstract: More than 4000 hourly wind profiles measured on three topographically different foredunes are analysed and discussed. Wind flow over the foredunes is studied by means of the relative wind speed: the ratio between wind speed at a certain location and the reference wind speed at the same height. Relative wind speeds appear to be independent of general wind speed but dependent on wind direction. For perpendicular onshore winds the flow over the foredune is accelerated due to topographic changes and decelerated du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
135
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 13 publications
25
135
0
1
Order By: Relevance
“…Further field research into airflow patterns in dune systems (e.g. Arens et al, 1995;Frank and Kocurek, 1996;Hesp, 2002;Kocurek et al, 1992;Tsoar, 1983;Walker, 1999;Walker and Nickling, 2002) as well as wind tunnel studies and numerical modelling (Parsons et al, 2004a,b;Schatz and Herrmann, 2006 ;van Boxel et al, 1999;Walker and Nickling, 2003) has yielded a more detailed understanding of lee-side air flow. The three broad categories--attached and undeflected flow, attached and deflected flow, and separated flow--determined by Sweet and Kocurek (1990) and modified by Walker and Nickling (2002) are dependent primarily on dune topography and the approach angle of the wind.…”
Section: Introductionmentioning
confidence: 99%
“…Further field research into airflow patterns in dune systems (e.g. Arens et al, 1995;Frank and Kocurek, 1996;Hesp, 2002;Kocurek et al, 1992;Tsoar, 1983;Walker, 1999;Walker and Nickling, 2002) as well as wind tunnel studies and numerical modelling (Parsons et al, 2004a,b;Schatz and Herrmann, 2006 ;van Boxel et al, 1999;Walker and Nickling, 2003) has yielded a more detailed understanding of lee-side air flow. The three broad categories--attached and undeflected flow, attached and deflected flow, and separated flow--determined by Sweet and Kocurek (1990) and modified by Walker and Nickling (2002) are dependent primarily on dune topography and the approach angle of the wind.…”
Section: Introductionmentioning
confidence: 99%
“…These actions create unvegetated gaps in the dune crest. As wind direction becomes more nearly parallel to a beach/dune contact, much of the sediment moves alongshore rather than into the dune (Sarre, 1989;Arens et al, 1995). An exception is where gaps in the crest increase local wind speeds and sand transport rates, making portions of the dune landward of them susceptible to inundation by wind-blown sand (Rosen, 1979;Gares and Nordstrom, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Bradley (1983) and found an inverse relationship between incident flow direction and speed, such that when the flow was more oblique to the dune crestline, the flow speed decreased over the dune (cf. Arens, 1995;1996;Lynch et al, 2010;Jackson et al, 2011), which implies that less sand can be delivered to the foredune crest and lee-side region. Arens et al (1995) found that, as winds became more oblique, the effective slope (i.e., aspect ratio) diminished and, in response, transport rates up the stoss slope decreased because topographically-forced flow acceleration is not as pronounced as with perpendicular approach angles.…”
mentioning
confidence: 99%
“…For flow approaching a steep, 70-to 90-m high scarp at an angle of 45° to normal, it was found that flow separated in front of the scarp base and was deflected alongshore, while higher up the scarp the flow crossed at an oblique angle. Arens et al (1995) argued that flow deflection increased with increasing foredune height. They found…”
mentioning
confidence: 99%